Characterization of the oxidative stress response regulatory network in Bacteroides fragilis: An interaction between BmoR and OxyR regulons promotes abscess formation in a model of intra-abdominal infection. (December 2022) - Teixeira, Felipe L.; Costa, Scarlathe B.; Pauer, Heidi; de Almeida, Bruno J.; Oliveira, Ana Carolina S.C.; Smith, C. Jeffrey; Domingues, Regina M.C.P.; Rocha, Edson R.; Lobo, Leandro A.
Abstract: Objectives: Bacteroides fragilis is an anaerobic bacterium that is commonly found in the human gut microbiota and an opportunistic pathogen in extra-intestinal infections. B. fragilis displays a robust response to oxidative stress which allows for survival in oxygenated tissues such as the peritoneal cavity and lead to the formation of abscesses. In this study, we investigated the synergy of the oxidative stress response regulators OxyR and BmoR in the ability of B. fragilis to resist oxidative damage and to survive in extra-intestinal infection. Methods: A Δ bmoR Δ oxyR double mutant B. fragilis strain was constructed, and its oxidative stress response was compared to parental and single mutant strains in phenotypical assays and gene expression analysis. The pathogenic potential in an in vivo mouse model of abscess formation was also evaluated. Results: Expression analysis showed a coordinated control of thioredoxin C ( trxC ) gene expression by BmoR and OxyR during oxygen exposure, with upregulation of trxC in the bmoR mutant strain (4.9-fold increase), downregulation in the oxyR mutant (2.5-fold decrease), and an intermediate level of deregulation (2-fold increase) in the double mutant strain compared to the parent strain. Expression analysis during oxidative stress conditions also showed that BmoR is a major repressor of the CoA-disulfide reductase gene (upregulated 47-fold in the bmoR mutant) while OxyR plays a minor repression role in this gene (upregulated 2.5-fold in the oxyR mutant). Exposure to atmospheric oxygen for up to 72 h revealed that the deletion of bmoR alone had no significant effect in in vitro survival phenotype assays, though it partially abolishes the OxyR sensitivity phenotype in the bmoR/oxyR double mutant strain compared to oxyR mutant. In vivo assays showed that bmoR and oxyR mutants were significantly impaired in the formation and development of abscesses compared to the parent strain in an experimental intra-abdominal infection mouse model. Conclusion: Although the full extent of genes whose expression are modulated by BmoR and OxyR is yet to be defined, we present evidence that these regulators have overlapping functions in B. fragilis response to oxidative stress and ability to form abscess in extra-intestinal tissues. Highlights: BmoR and OxyR have overlapping functions in B. fragilis oxidative stress response. Deletion of bmoR and/or oxyR impairs abscess formation in mice. BmoR and OxyR co-regulates thioredoxin C and CoA-disulfide reductase genes. Long exposure to O2 shows phenotypic antagonism between BmoR and OxyR. Absence of the bmoR gene enhances sensitivity to oxygen.